Cyclic magnetite dissolution in Pleistocene sediments of the abyssal northwest Pacific Ocean: Evidence for glacial oxygen depletion and carbon trapping. (24th May 2016) - Korff, Lucia; von Dobeneck, Tilo; Frederichs, Thomas; Kasten, Sabine; Kuhn, Gerhard; Gersonde, Rainer; Diekmann, Bernhard
Abstract: The carbonate‐free abyss of the North Pacific defies most paleoceanographic proxy methods and hence remains a "blank spot" in ocean and climate history. Paleomagnetic and rock magnetic, geochemical, and sedimentological methods were combined to date and analyze seven middle to late Pleistocene northwest Pacific sediment cores from water depths of 5100 to 5700 m. Besides largely coherent tephra layers, the most striking features of these records are nearly magnetite‐free zones corresponding to glacial marine isotope stages (MISs) 22, 12, 10, 8, 6, and 2. Magnetite depletion is correlated with organic carbon and quartz content and anticorrelated with biogenic barite and opal content. Within interglacial sections and mid‐Pleistocene transition glacial stages MIS 20, 18, 16, and 14, magnetite fractions of detrital, volcanic, and bacterial origin are all well preserved. Such alternating successions of magnetic iron mineral preservation and depletion are known from sapropel‐marl cycles, which accumulated under periodically changing bottom water oxygen and redox conditions. In the open central northwest Pacific Ocean, the only conceivable mechanism to cause such abrupt change is a modified glacial bottom water circulation. During all major glaciations since MIS 12, oxygen‐depleted Antarctic Bottom Water (AABW)‐sourced bottom water seems to have crept into the abyssal northwest Pacific below ~5000 m depth, thereby changing redox conditions in the sediment, trapping and preserving dissolved and particulate organic matter and, in consequence, reducing and dissolving both, biogenic and detrital magnetite. At deglaciation, a downward progressing oxidation front apparently remineralized and released these sedimentary carbon reservoirs without replenishing the magnetite losses. Key Points: Abyssal northwest Pacific records show cyclic glacial magnetite dissolution zones Evidence for glacial carbon trapping in sediment followed by deglacial CO2 release Changing LCDW/AABW partitioning from Atlantic to Pacific after mid‐Pleistocene transition